Antibiotic prescribing for endodontic infections: a survey of dental students in Italy. (10th May 2019) - Salvadori, M.; Audino, E.; Venturi, G.; Garo, M. L.; Salgarello, S.
Abstract: Aim: To determine the knowledge of final year undergraduate students attending Italian universities on the appropriate use of systemic antibiotics for endodontic infections. Methodology: Final year dental students from twenty Italian universities completed a one‐page questionnaire on antibiotic use for the treatment of endodontic infections. Data were analysed using descriptive statistics and chi‐square tests. Results: A total of three hundred and three students completed the questionnaire. The average duration of antibiotic prescription proposed by respondents was 5.48 ± 1.06 days. Amoxicillin with clavulanic acid was the first‐choice antibiotic (85.2%) followed by amoxicillin alone (13.5%), azithromycin (1.0%) and clarithromycin (0.3%), for patients not allergic to penicillin. Clarithromycin was the first‐choice drug for patients with a penicillin allergy (56.1%), followed from azithromycin (31.7%), clindamycin (11.9%) and levofloxacin (0.3%). Alveolar abscess with systemic manifestations was reported as the principal reason to prescribe antibiotics (97.7%) followed by the same condition without systemic manifestations (85.5%). For the scenario of irreversible pulpitis, 5% of students considered antibiotics necessary. Almost 52% of students would prescribe antibiotics for apical acute periodontitis; 29.7% would prescribe antibiotics for chronic apical periodontitis with sinus tract, and 13.5% indicated these drugs for chronic apical periodontitis without sinus tract. Conclusions: The results demonstrate that it is necessary to improve the knowledge of Italian students on antibiotics and indications for their use in endodontics.